Implementation of the Agribusiness System and Feasibility of Rice Farming - Umbu Joka; Boanerges Sipayung; Achmad S Maulana; Campina Illa Prihantini; Fransiskus Dewa Kadju; Jullyo G Rohi (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2024)
Rice farming in TTU Regency is not only a source of livelihood but also has deep cultural values. The process of farming and harvesting rice plants is often a joint event that strengthens social ties. Rice farming is considered one of the basic and cultural foundations for the agricultural community of TTU Regency. This research aims to determine the implementation of the agribusiness system and the feasibility of lowland rice farming in the East Noemuti District. Primary data was obtained from interviews, documentation, questionnaires and surveys. Meanwhile, researchers obtained secondary data from various references such as journals, theses, books and the Central Statistics Agency. The population of this study was 400 people. The sampling technique used in this research is purposive sampling where the data source is taken with certain considerations. The number of samples in this study was 101 people. The data analysis used by researchers is descriptive analysis and farming feasibility analysis. Research results based on survey results found that farmers in East Noemuti District have implemented the agribusiness system well, although not yet optimally. The results of the feasibility analysis using a cost analysis approach show that lowland rice farming in East Noemuti District is feasible with an R/C Ratio value of 4.0.